Alpha lipoic acid treatment induces the antioxidant system and ameliorates lipid peroxidation in maize seedlings under osmotic stress - Terzi, Rabiye; Saruhan Güler, Neslihan; Güven, Funda Gül; Kadioglu, Asim (Archives of Biological Sciences, 2018)
Paper description: Exogenous alpha lipoic acid (ALA) plays a role in promoting salt tolerance in plants. However, the effects of ALA application on the antioxidant system have not been sufficiently clarified in plants exposed to abiotic stresses. The effects of ALA application on the activities of antioxidant enzymes and membrane damage were investigated in maize seedlings under osmotic stress. ALA application elevated activities of antioxidant enzymes and ameliorated lipid peroxidation. Exposure to ALA improves resistance against osmotic stress by inducing the antioxidant system in maize. Abstract: Plants are markedly affected by drought stress caused by fluctuations in global climate, reduction in rainfall and a decrease in soil fertility. Therefore, some mechanistic strategies to cope with adverse effects of drought stress are needed. Alpha lipoic acid (ALA), a potent antioxidant molecule, is known to function in abiotic stress tolerance. In the current study, we investigated the ALA-stimulated physiological role in tolerance to osmotic stress induced by polyethylene glycol in two maize (Zea mays L.) cultivars (cv. Helen and cv. Akpinar). Application of ALA increased the leaf water potential of maize cultivars under stressful and stress-free conditions but decreased lipid peroxidation and the hydrogen peroxide (H2O2) content. Additionally, enhanced activity of the antioxidant defense system was observed following ALA application. Exogenous ALA elevated the activities of enzymatic antioxidants such as superoxide dismutase (SOD), catalase (CAT), guaiacol peroxidase (GPX), glutathione reductase (GR) and monodehydroascorbate reductase (MDHAR) under osmotic stress as compared to seedlings not exposed to ALA. Conversely, ascorbate peroxidase (APX) activity was decreased by ALA application in both cultivars. Higher GR and MDHAR activities of both cultivars were simultaneously observed in ALA treatments under osmotic stress. Taken together, the data indicated that exogenous ALA may function in arranging resilience against osmotic stress by reducing oxidative damage through induction of the antioxidant machinery in maize cultivars. https://doi.org/10.2298/ABS171218011T Received: December 18, 2017; Revised: February 22, 2018; Accepted: March 20, 2018; Published online: April 4, 2018 How to cite this article: Terzi R, Saruhan Güler N, Güven FG, Kadioglu A. Alpha lipoic acid treatment induces the antioxidant system and ameliorates lipid peroxidation in maize seedlings under osmotic stress. Arch Biol Sci. 2018;70(3):…